2018
DOI: 10.1080/17408989.2018.1485143
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the relationship between educational background and the coaching behaviours and practice activities of professional youth soccer coaches

Abstract: Background and Purpose Despite the proliferation in recent years of higher education establishments offering tertiary-level study in the field of sports coaching, there is a lack of research into the impact of such courses on coaching practice. The behaviours employed and activities used by coaches during practice sessions is an area where one might expect to see such impact, indeed certain studies have tentatively noted the educational qualifications of coaches and suggested that this may play a role in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
3
26
1
2
Order By: Relevance
“…Unique to this cricket context due to the changing role between coach and player was involvement in training (1.3%), in addition to less commonly seen behaviours such as feeding (1.2%) and conferring with players (2.9%). The manner in which the player-coach interacts with their players appears to differ to that of non-player coaches from previous research (Hall et al, 2016;Stonebridge & Cushion, 2018).…”
Section: Presenter Biographycontrasting
confidence: 78%
“…Unique to this cricket context due to the changing role between coach and player was involvement in training (1.3%), in addition to less commonly seen behaviours such as feeding (1.2%) and conferring with players (2.9%). The manner in which the player-coach interacts with their players appears to differ to that of non-player coaches from previous research (Hall et al, 2016;Stonebridge & Cushion, 2018).…”
Section: Presenter Biographycontrasting
confidence: 78%
“…Note that in the present study, we performed only the Step 1 of a modified version of the "Coach Analysis and Intervention System" (CAIS) (see Table 2) due to the reason that we analyzed the verbal behaviors used by the coach during the main part of the training (excluding warm up and cool down). Previous studies (Cushion et al, 2012;Stonebridge and Cushion, 2018;Eather et al, 2020) have confirmed the validity and reliability of CAIS in the context of study of verbal behavior in youth soccer.…”
Section: Methodsmentioning
confidence: 69%
“…Another study provided corresponding findings with reference to professional football coaches for under 10 and under 16 players, albeit with a smaller gap between TF (53%) and PF (47%) [16]. Two newer football studies involving youth athletes demonstrated that most time was devoted to PF, followed by transition and TF [14,15]. The professional coaches for under 9-under 18 athletes devoted more than half of the session time to PF (57%), followed by TF (21%) and others (22%) [15], whereas club level under 11-under 17 teams utilized less than half the time on PF (41%), followed by inactivity (37%) and TF (22%) [14].…”
Section: Introductionmentioning
confidence: 85%
“…PF refers to match-like practice activities, involving games or tactical aspects, while TF denotes drill-like practice activities, involving physical or technical aspects. Some studies added a 'transition/other' category, for activities that were neither PF nor TF (e.g., water break) [11,12,14,15].…”
Section: Introductionmentioning
confidence: 99%